A imigração haitiana no município de Palotina PR, 2010-2017 imigrasyon ayisyen yo nan vil Palotina, 2010-2017 - Manfrin, Ionara Ana (2019)
The research sought to analyze the recent Haitian immigration to Brazil, especially to the municipality of Palotina, in the State of Paraná PR, 2010-2017, with information about the motivations that led the Haitians to immigrate and how it occurred the territorialization of these in Palotinean society. Through specific literature and field surveys, we sought to reflect on the interrelationships between work and migration in contemporary times. It was also discussed the processes of territorialization and territoriality that is materializing from the presence of these migrants, who left their native land in search of better living conditions.